Conditional disruption of IGF-I gene in type 1α collagen-expressing cells shows an essential role of IGF-I in skeletal anabolic response to loading - Kesavan, Chandrasekhar (American Physiological Society, 2011)
To establish a causal role for locally produced IGF-I in the mechanical strain response in the bone, we have generated mice with conditional disruption of the insulin-like growth factor (IGF) I gene in type 1α(2) collagen-expressing cells using the Cre-loxP approach. At 10 wk of age, loads adjusted to account for bone size difference were applied via four-point bending or axial loading (AL) in mice. Two wk of bending and AL produced significant increases in bone mineral density and bone size at the middiaphysis of wild-type (WT), but not knockout (KO), mice. In addition, AL produced an 8–25% increase in trabecular parameters (bone volume-tissue volume ratio, trabecular thickness, and trabecular bone mineral density) at the secondary spongiosa of WT, but not KO, mice. Histomorphometric analysis at the trabecular site revealed that AL increased osteoid width by 60% and decreased tartrate-resistance acidic phosphatase-labeled surface by 50% in the WT, but not KO, mice. Consistent with the in vivo data, blockade of IGF-I action with inhibitory IGF-binding protein (IGFBP4) in vitro completely abolished the fluid flow stress-induced MC3T3-E1 cell proliferation. One-way ANOVA revealed that expression levels of EFNB1, EFNB2, EFNA2, EphB2, and NR4a3 were different in the loaded bones of WT vs. KO mice and may, in part, be responsible for the increase in bone response to loading in the WT mice. In conclusion, IGF-I expressed in type 1 collagen-producing bone cells is critical for converting mechanical signal to anabolic signal in bone, and other growth factors cannot compensate for the loss of local IGF-I.